2013
DOI: 10.1007/s10443-013-9354-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of the Effect of Material Randomness on the Damage Behaviour of CFRP Laminates with Stochastic Cohesive-Zone Elements

Abstract: This raises the question of whether the inherent stochasticity of localised damage is of significance in terms of the global properties and design methods for such materials. This paper presents the numerical modelling based analysis of the effect of material randomness on delamination damage in CFRP materials by the implementation of stochastic cohesive-zone model (CZM) within the framework of the finite-element (FE) method. The initiation and propagation of delamination in a unidirectional CFRP double-cantil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…When investigating the stochastic fracture toughness effect on the delamination process of a DCB specimen, Ashcroft et al assumed the initial stiffness and fracture toughness to be proportional to the interface strength. [14][15][16][17] Similar approach was adopted in the present work (Figure 5), and the critical and failure separation of the cohesive interface were taken as 0 ¼ 10 À9 m and f ¼ 2 Â 10 À7 m (the two values were chosen by consulting parameter dimension in the literatures 7,9,10 ), respectively. To promote the solution convergence, a viscosity coefficient of 2 Â 10 À4 taken from O'Dwyer et al 7 was used.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…When investigating the stochastic fracture toughness effect on the delamination process of a DCB specimen, Ashcroft et al assumed the initial stiffness and fracture toughness to be proportional to the interface strength. [14][15][16][17] Similar approach was adopted in the present work (Figure 5), and the critical and failure separation of the cohesive interface were taken as 0 ¼ 10 À9 m and f ¼ 2 Â 10 À7 m (the two values were chosen by consulting parameter dimension in the literatures 7,9,10 ), respectively. To promote the solution convergence, a viscosity coefficient of 2 Â 10 À4 taken from O'Dwyer et al 7 was used.…”
Section: Model Developmentmentioning
confidence: 99%
“…Failure process of materials with stochastic local property is significantly different from that of identical cases. Ashcroft et al [14][15][16][17] investigated the random fracture toughness effect on the delamination process of a double cantilever beam (DCB) specimen with stochastic cohesive element and concluded that the microstructural randomness could significantly affect the macroscopic delamination process of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, variability in bonding properties might also be attributed to inherent surface defects in pregreg due to the fabrication process. Several studies have focused on the overall mechanical response of materials ( Dimas et al, 2016( Dimas et al, , 2015( Dimas et al, , 2014 or interface ( Taleb Ali et al, 2018;Xu et al, 2014;Motamedi et al, 2013;Khokhar et al, 2009Khokhar et al, , 2013Jumel, 2017 ) subjected to propertys heterogeneity induced by cracks, defects, or other types of flaws, and it was found that the material or bonding strengths are sensitive to randomly distributed properties.…”
Section: Introductionmentioning
confidence: 99%